If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 = 2 + 3u Solving 20 = 2 + 3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3u' to each side of the equation. 20 + -3u = 2 + 3u + -3u Combine like terms: 3u + -3u = 0 20 + -3u = 2 + 0 20 + -3u = 2 Add '-20' to each side of the equation. 20 + -20 + -3u = 2 + -20 Combine like terms: 20 + -20 = 0 0 + -3u = 2 + -20 -3u = 2 + -20 Combine like terms: 2 + -20 = -18 -3u = -18 Divide each side by '-3'. u = 6 Simplifying u = 6
| (7x^4)/(sqrt(2x-8)) | | 2.3log(x)=3log(6-x) | | 6x+y+z=10 | | -4u+5=5-4u | | 1920*x=5 | | -15=4u-3 | | 4lnx-1=6 | | 5/4=7x^2-x | | 42+x=(13+x)*2 | | 21y+7=5 | | 5/2*32 | | Y=-xy-3x-3 | | 11=2/3x-3 | | 2y=5y-8 | | 1920*x=2 | | x-(0.75x+1)=1 | | 4=4xW | | 4x^3+18x=0 | | 7-3-2/5v | | 3x-(x+1)=9 | | x+55=4x-5 | | 0=60+12.5x-4.9x^2 | | -16+3=-24+8x | | 3x*5y=1450 | | 15y+20x=525 | | 30+9k=3(4k+7) | | 42+x=(13+x).2 | | (b+6)(b+4b)= | | r^3+3y^2-4=0 | | -7+35=207x | | 19y+9=y-351 | | x/1=9 |